Who was Nyerere? The Mythical Recreation of Nyerere the Person in Banyakyusa Narratives - Fedeo, Ignas; Kiyimba, Abasi; Okot, Benge (ELS Journal on Interdisciplinary Studies in Humanities, 2020)
Abstract Asking about who Nyerere was is obviously a surprising option in this century especially when we pay a particular attention to literatures devoted to his life and career. A number of politicians and scholars have written in length on Nyerere’s individual life and his political career. However, the question remains significant on the sense that irrespective of the Nyerere we know from politicians and academicians’ perspectives, little is known about him in the perceptions and beliefs of local Tanzanians. By looking at the Banyakyusa process of mythmaking about Nyerere, this qualitative study examines images and symbols associated with Nyerere’s nature. The paper interrogates Banyakyusa voice, beliefs and point of views on Nyerere’s personality embedded in their mythical narratives. To Banyakyusa, as the paper establishes, Nyerere was endowed with supernatural powers including immense mystical abilities by which he was able to foresee the future and to protect himself against his enemies. Also, Nyerere was blessed with inborn intelligent abilities. The abilities made him be able to train himself various skills such as reading, writing and counting. In general, the recreation of Nyerere’s personality in Banyakyusa myths reflects Banyakyusa traditional beliefs on powers and abilities of their traditional leaders.